2022
DOI: 10.1262/jrd.2021-115
|View full text |Cite
|
Sign up to set email alerts
|

Mouse <i>in vivo</i>-derived late 2-cell embryos have higher developmental competence after high osmolality vitrification and −80°C preservation than IVF or ICSI embryos

Abstract: Mammalian embryos are most commonly cryopreserved in liquid nitrogen; however, liquid nitrogen is not available in special environments, such as the International Space Station (ISS), and vitrified embryos must be stored at −80 °C. Recently, the high osmolarity vitrification (HOV) method was developed to cryopreserve mouse 2-cell stage embryos at −80 °C; however, the appropriate embryo is currently unknown. In this study, we compared the vitrification resistance of in vivo-derived, in vitro fertilization (IVF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
(39 reference statements)
1
7
0
Order By: Relevance
“…To evaluate embryo quality using this system, morulae/blastocysts cultured for 3 days in ETC were transferred to mice. In a control experiment in which 2-cell stage embryos removed immediately after thawing in the ETC, were transferred to the oviduct of the recipient female, we showed a birth rate of 47%, which was comparable to birth rates of our usual frozen-thawed embryos [21]. When embryos collected after 3 days of culture in the ETC were transferred to the uterus, birth rate was 31%, which was slightly lower than the control (Table 4).…”
Section: Plos Onesupporting
confidence: 52%
See 1 more Smart Citation
“…To evaluate embryo quality using this system, morulae/blastocysts cultured for 3 days in ETC were transferred to mice. In a control experiment in which 2-cell stage embryos removed immediately after thawing in the ETC, were transferred to the oviduct of the recipient female, we showed a birth rate of 47%, which was comparable to birth rates of our usual frozen-thawed embryos [21]. When embryos collected after 3 days of culture in the ETC were transferred to the uterus, birth rate was 31%, which was slightly lower than the control (Table 4).…”
Section: Plos Onesupporting
confidence: 52%
“…However, the embryo recovery rate obtained by the ETC was lower than that shown in this study (submitted). We tried various improvements right up to launch, such as a good equilibration medium for embryo culture in ETC [20], and identified the most appropriate stage of mouse two-cell embryos for the present project [21]. However, space experiments can be challenging.…”
Section: Discussionmentioning
confidence: 99%
“…The first two cleavage events in an embryo take approximately 20 hours each, and these are significantly longer than successive cleavage steps which take approximately 12 hours each to complete (Mihajlović & Bruce, 2017). The main disadvantage of trying to produce metaphase spreads from IVF-produced two-cell embryos was that many embryos were developmentally arrested before the division into four-cells, and thus did not progress through to metaphase (Hayashi et al, 2022). In general, 10-15% of all human embryos made via IVF arrest at this two-cell stage mainly due to a build-up of reactive oxygen species (ROS) (Betts & Madan, 2008).…”
Section: Ivf Produced Embryosmentioning
confidence: 99%
“…Two-cell embryos produced from timed matings can be flushed at the later stages of the cell cycle (i.e., on the cusp of division to four-cells) making them an ideal sample type for metaphase spread preparation (Bedford, 1971). It has also been shown that late stage two-cell embryos collected via embryo flushing have a higher chance of survival in comparison to early stage two-cell embryos (Hayashi et al, 2022). Early stage two-cell embryos have a higher chance of remaining in interphase (S or G2 phase of the cell cycle) in comparison to dividing late stage two-cell embryos (Hayashi et al, 2022).…”
Section: Flushed Embryosmentioning
confidence: 99%
See 1 more Smart Citation